Effectiveness of Cognitive Behavioral Group Intervention on Body Image Improving and Increasing Self-Esteem in Women with Breast Cancer after Mastectomy - Ahmad Izadi-Ajirlo; Bahman Bahmani; Ali Ghanbari-Motlagh (Journal of Rehabilitation, 2013)
Objective: This study was conducted to improve the body image and self-esteem among breast cancer patients after mastectomy.